Glutamatergic neurons and GABAergic neurons of medial prefrontal cortex control hoarding-like behavior - Xiong, Yujie; Wang, Beining; Shang, Yunxia; Liu, Huan; Zhan, Zihao; Xu, Qi; Wang, Kai; Zhang, Zhi; Sun, Tingting (Frontiers in Neuroscience, 2023)
Hoarding disorder (HD) is a chronic disease that begins early in life and does not remission unless timely treated. A large number of factors affect the presentation of HD symptoms, including a strong possessive psychology of objects and neurocognitive functioning. However, the underlying neural mechanisms of the excessive hoarding behavior in HD are still unknown. Using viral injections and brain slice electrophysiology recordings, we found that increased glutamatergic neuronal activity and decreased GABAergic neuronal activity in medial prefrontal cortex (mPFC) accelerated the hoarding-like behavior in mice. Respectively, chemogenetic manipulation to reduce glutamatergic neuronal activity or enhance GABAergic neuronal activity could improve the hoarding-like behavioral response. These results reveal a critical role played by alterations in the activity of specific types of neurons in hoarding-like behavior, and that targeted therapies for HD may be possible by precisely modulating these types of neurons.